2021
DOI: 10.3390/su132313250
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of a World Heritage Site in Terms of Conservation and Tourism Promotion: The Case of “Ibiza, Biodiversity and Culture” (Ibiza, Spain)

Abstract: United Nations Educational, Scientific and Cultural Organization (UNESCO) World Heritage Sites (WHS) have great prestige. Each year, candidatures are presented by advocates seeking to raise awareness of the importance of certain cultural and natural sites, to achieve better protection and to make them known, which can promote tourism to benefit the surrounding regions. One of these cases is Ibiza, which, after a first rejection in 1986, obtained the inscription of “Ibiza, Biodiversity and Culture” in 1999. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Firstly, in this study, we identified a causal effect of cultural heritage on overall economic growth. There exists an extensive sociological work exploring the association between World Cultural Heritage sites and tourism economy-other than the overall economic status-such as conservation and tourism promotion [4], tourism demand [52], sustainable tourism management [51], and resource curse in tourism economies [2]. As for realizing the causal inference of cultural heritages on the tourism economy, much evidence supports the tourist-enhancing effect of World Cultural Heritage [76,77], while some empirical results are conflicting [53,78,79].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, in this study, we identified a causal effect of cultural heritage on overall economic growth. There exists an extensive sociological work exploring the association between World Cultural Heritage sites and tourism economy-other than the overall economic status-such as conservation and tourism promotion [4], tourism demand [52], sustainable tourism management [51], and resource curse in tourism economies [2]. As for realizing the causal inference of cultural heritages on the tourism economy, much evidence supports the tourist-enhancing effect of World Cultural Heritage [76,77], while some empirical results are conflicting [53,78,79].…”
Section: Discussionmentioning
confidence: 99%
“…Cultural heritage is closely linked to various areas of sustainable development goals, such as environmental, social, and economic issues [1]. Specifically, World Cultural Heritage(s) (WCH) sites play significant roles in economic activities, such as the tourism economy, culture economy, circular economy, and low-carbon economy [2][3][4]. However, the impact of the WCH acquisition on economic growth has not been thoroughly attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Indonesia is an archipelagic country consisting of thousands of islands ( 73 ) and has a variety of tribes, languages, customs, and cultures. UNESCO has begun documenting the culture of all countries in the world as World Cultural Heritage (World Heritage) ( 74 76 ). Ramón-Cardona et al ( 74 ) state that understanding the significance of specific cultural and natural sites to enhance their conservation and raise awareness can encourage tourism and benefit the surrounding area.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…UNESCO has begun documenting the culture of all countries in the world as World Cultural Heritage (World Heritage) ( 74 76 ). Ramón-Cardona et al ( 74 ) state that understanding the significance of specific cultural and natural sites to enhance their conservation and raise awareness can encourage tourism and benefit the surrounding area. Gański ( 77 ) states that tourists are attracted mainly by the rich historical and cultural heritage.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…It is necessary to have an active and thoughtful attitude toward the settlements in this area, which can preserve their tourism potential and resources, in order to avoid actions that could contribute to their degradation and to develop those that enable the area's full inclusion in modern life. First of all, the contribution to the above can be made through construction patterns, but also through the tourism potential that can be activated [33]. Current procedures toward the renewal and reconstruction of existing structures, as well as the construction of new facilities, are based on the preservation of the vernacular appearance of structures in rural settlements [34] through the improvement of bioclimatic characteristics and the application of new technological possibilities.…”
Section: Architectonic and Technological Aspects In The Preservation ...mentioning
confidence: 99%